2019
DOI: 10.1177/0954406219890368
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness modeling, identification, and measuring of a rotating spindle

Abstract: The stiffness of a spindle at high speeds has a significant effect on the quality of the cutting surface and the machining accuracy. However, the spindle stiffness is difficult to be detected directly when the spindle is rotating, and the measured stiffness values are usually coupled with other parts of the spindle–tool system (such as toolholder, spindle–toolholder joint, tool). This paper presents a comprehensive method to deal with the stiffness modeling, identification, and measuring of a rotating spindle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…As the ball is loaded in ring raceway, the friction moment generated by ceramic material energy elastic hysteresis is shown in equation (6).…”
Section: Thermal Deformation Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…As the ball is loaded in ring raceway, the friction moment generated by ceramic material energy elastic hysteresis is shown in equation (6).…”
Section: Thermal Deformation Calculationmentioning
confidence: 99%
“…[1][2][3] However, there exists complex distribution of thermal magnetic coupling in the ceramic spindle rotor system, leading to the variation of electromagnetic radial force, temperature and dynamic characteristics of the rotor system, which directly affect the precision machining quality of motorized spindle. [4][5][6] To improve the accuracy of the dynamic model, the thermal and magnetic fields factors need to be considered and modeled by finite element method.…”
Section: Introductionmentioning
confidence: 99%
“…So far, in terms of spindle with rolling bearings, the force displacement method is usually utilized to measure its spindle nose stiffness [9][10][11][12]. There are two loading methods: contact loading method [7][8][9][10]13] and non-contact loading method [11,12,[14][15][16]. The contact loading method generally applys an external load by machanical transmission, so the applied load can reach a large value.…”
Section: Introductionmentioning
confidence: 99%
“…Spindle stiffness of the machine tool, which reflects its capacity to resist deformation when subjected to external loads, is one of the most essential indicators for evaluating the service performance of a spindle [4][5][6]. Low spindle stiffness causes chatter [1], unwanted back cutting, and excessive cutter tilt, all of which affect the cutting surface quality [7][8][9] and the machining accuracy [10,11], as well as causing the rolling elements of the spindle bearing to slip, aggravating spindle component wear [12] and weakening machine tool reliability [13][14][15]. As a result, high stiffness becomes one of the most important aims in precision machine tool spindle design [16].…”
Section: Introductionmentioning
confidence: 99%
“…In order to better investigate the effect of dynamic effects generated by spindle operation on its static stiffness, A. Matsubara [22] designed a magnetic loading device to measure the radial operating stiffness of the spindle and found that the velocity and thermal effects can lead to significant softening and hardening characteristics in the spindle radial stiffness. Wang [10] proposed a three-step identification algorithm for spindle radial stiffness based on stiffness theory modeling, which solves the difficult problem of the measured value being often coupled in the spindle-tool stiffness during spindle radial operating stiffness testing, and improves the accuracy of spindle radial operating stiffness testing. For drilling machines, vertical spindle surface grinders, and other axially loaded machine tools, the axial operating stiffness of the spindle system should be of increased importance throughout its entire life cycle.…”
Section: Introductionmentioning
confidence: 99%